Perceived need for information among patients with a haematological malignancy: associations with information satisfaction and treatment decision‐making preferences. Issue 2 (9th May 2014) - Rood, Janneke A. J.; van Zuuren, Florence J.; Stam, Frank; van der Ploeg, Tjeerd; Eeltink, Corien; Verdonck‐de Leeuw, Irma M.; Huijgens, Peter C.
Summary For patients with haematological malignancies, information on disease, prognosis, treatment and impact on quality of life is of the utmost importance. To gain insight into the perceived need for information in relation to sociodemographic and clinical parameters, comorbidity, quality of life (QoL) and information satisfaction, we compiled a questionnaire based on existing validated questionnaires. A total of 458 patients diagnosed with a haematological malignancy participated. The perceived need for information was moderate to high (40–70%). Multivariate regression analyses showed that a higher need for information was related to younger age, worse QoL, being member of a patient society and moderate comorbidity. The need for disease and treatment‐related information was higher than the need for psychosocial information. A higher need for disease and treatment‐related information was associated to being diagnosed with multiple myeloma. A higher need for psychosocial information was related to a lower educational level. The information provision could be improved according to 41% of the patients. Higher satisfaction with provided information was associated with better QoL. Most patients (62%) reported that they wanted to be fully informed about their illness and actively involved in treatment decision‐making. The results contribute to improving patient‐tailored information provision and shared decision‐making in clinical practice. Copyright © 2014 John Wiley & Sons, Ltd.